1987
DOI: 10.2307/352679
|View full text |Cite
|
Sign up to set email alerts
|

Family and Friends as Social Environments and Their Relationship to Young Adolescents' Use of Alcohol, Tobacco, and Marijuana

Abstract: This study examines the role of family and friends in accounting for alcohol, tobacco, and marijuana use among young adolescents. The sample included 1,008 males and 1,040 females with a mean age of 14.5 years. Lack of parental affection, concern, involvement, and modeling appeared to be centralfactors in the family's influence, which accounted for up to 22% of the variance in drug use. Friends' delinquency and use of drugs largely determined the influence of friendship, which accounted for up to 40% of adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(85 citation statements)
references
References 52 publications
5
79
0
1
Order By: Relevance
“…) In "two social worlds" theories, parents and peers are portrayed as operating primarily in isolation from each other. The infl uence of parents and peers is seen as distinct, with little or no overlap in the quality of relationships across the two settings (Berndt, 1979;Coleman, 1960;Greenberg, Siegel, & Leitch, 1983;Hundleby & Mercer, 1987;Kandel et al, 1978). Similarly, cognitive theorists such as Piaget (1932Piaget ( /1965 and Sullivan and Sullivan (1980) contended that social relationships with peers contribute to adolescent development in ways unique from those with parents.…”
Section: Theories Of Weak Parent-peer Linkages During Adolescencementioning
confidence: 99%
“…) In "two social worlds" theories, parents and peers are portrayed as operating primarily in isolation from each other. The infl uence of parents and peers is seen as distinct, with little or no overlap in the quality of relationships across the two settings (Berndt, 1979;Coleman, 1960;Greenberg, Siegel, & Leitch, 1983;Hundleby & Mercer, 1987;Kandel et al, 1978). Similarly, cognitive theorists such as Piaget (1932Piaget ( /1965 and Sullivan and Sullivan (1980) contended that social relationships with peers contribute to adolescent development in ways unique from those with parents.…”
Section: Theories Of Weak Parent-peer Linkages During Adolescencementioning
confidence: 99%
“…For example, of all family members, mothers had the most negative feelings about having someone in the family drop out (Bachman et al, 1971). A mother's willingness to be involved with her child is also likely to be inversely related to hostility and rejection; this maternal nurturance was correlated with lower adolescent drug use and deviance (Hundleby, Mercer, & Guelph, 1987). In summary, negative parental attitudes and behaviors are correlated with greater school drop-out and substance use, and maternal attitudes and behaviors may be of greatest import.…”
mentioning
confidence: 97%
“…Children raised in families with lax supervision or excessively severe or inconsistent disciplinary practices are at risk for later substance abuse (Baumrind, 1985 Hundleby and Mercer (1987) found that adolescents' reports of parental trust, concern and involvement were negatively related to the extent of tobacco, alcohol and marijuana use, explaining between 3% and 8% of the variance. in an earlier study, Mercer and co-workers (19780 found that adolescent reports of parental warmth, support and interest were negatively related to the extent of tobacco and alcohol use by both males and females, but significantly related to marijuana use only for females.…”
Section: Family Management Problemsmentioning
confidence: 99%